Development and validation of the short form of the Later Life Workplace Index: a study across 10 countries - Finsel, Julia S.; Axelrad, Hila; Choi, Su Jung; Derous, Eva; Gu, Xiuzhu; Guandalini, Paolo; Ha, Jaeyoung; Kim, Eun Seok; Marzec, Izabela; Mykletun, Reidar J.; Oliveira, Eduardo; Pajic, Sofija; et al. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
This study aims to develop and validate a short form of the Later Life Workplace Index (LLWI). The LLWI measures organizational practices relevant to older workers’ ability, motivation, and opportunity to continue working in later life. It consists of nine domains comprising three to four conceptual indicators each. We applied a combined qualitative and quantitative strategy to reduce the original LLWI 80-item measure into a 29-item short form (LLWI-SF). Different language versions were developed and applied to samples in ten countries: Belgium (N = 444), Germany (N = 387), Italy (N = 408), Japan (N = 349), Korea (N = 350), Norway (N = 140), Poland (N = 353), Portugal (N = 306), the Netherlands (N = 317), and the United States (N = 370). Our data provides evidence for the reliability and validity of the LLWI-SF in the ten countries and languages. Moreover, partial measurement invariance of the LLWI-SF is supported despite the diverging regulatory and cultural contexts. Thus, we provide a short but holistic measure of organizational practices for older workers that can be efficiently used in research and practice.
Keywords: Human Resource Management; Scale Development; Measurement; Validation; Cross-Cultural Issue; Leadership